Isolation and partial characterization of Salmonella Gallinarum bacteriophage - ishnaiwer, murad (Saudi Journal of Biological Sciences, 2022)
Infections caused by Salmonella remain a major public health problem worldwide. Animal food products, including poultry meat and eggs, are considered essential components in the individual’s daily nutrition. However, chicken continues to be the main reservoir for Salmonella spp. Poultry farmers use several types of antibiotics to treat pathogens. This can pose a health risk as pathogens can build antibiotic resistance in addition to the possibility of accumulation of these antibiotics in food products. The use of phages in treating poultry pathogens is increasing worldwide due to its potential use as an effective alternative to antibiotics. Phages have several advantages over antibiotics; phages are very specific to target bacteria, less chances of developing secondary infections, and they only replicate at the site of infection. Here we report the isolation of a bacteriophage from chicken feces. The isolated bacteriophage hosts on Salmonella Gallinarum, a common zoonotic infection that causes fowl typhoid, known to cause major losses to poultry sector. The isolated bacteriophage was partially characterized as a DNA virus resistant to RNase digestion with approximately 20 Kb genome. SDS-PAGE analysis of total viral proteins showed at least five major bands (21, 28, 42, 55 and 68 kDa), indicating that this virus is relatively small compared to other known poultry phages. The isolated bacteriophage has the potential to be an alternative to antibiotics and possibly reducing antibiotic resistance in poultry farms.
Keywords: Salmonella Gallinarum Bacteriophage Poultry Phage therapy Antibiotic resistance